2021
DOI: 10.3390/agronomy11030432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Four Delineation Methods to Identify Potential Management Zones in a Commercial Potato Field in Eastern Canada

Abstract: Management zones (MZs) are delineated areas within an agricultural field with relatively homogenous soil properties, and therefore similar crop fertility requirements. Consequently, such MZs can often be used for site-specific management of crop production inputs. This study evaluated the effectiveness of four classification methods for delineating MZs in an 8-ha commercial potato field located in Prince Edward Island, Canada. The apparent electrical conductivity (ECa) at two depths from a commercial Veris sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
(84 reference statements)
1
6
0
Order By: Relevance
“…Thus, the two methods are significantly influenced by the sample distance. Several previous studies have reported similar conclusions [ 11 , 21 , 48 ]. However, the GMM map was different from that of FCM and ISODATA.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Thus, the two methods are significantly influenced by the sample distance. Several previous studies have reported similar conclusions [ 11 , 21 , 48 ]. However, the GMM map was different from that of FCM and ISODATA.…”
Section: Discussionsupporting
confidence: 82%
“…First, fertilization practices significantly influence soil available nutrients (e.g., AP and AK), which contributes to the accumulation of soil available nutrients [ 39 ]. The fertilizer application rate varied greatly in intensive farming systems, resulting in high variability of soil AP and AK [ 11 ]. In addition, the crop rotation systems in this study are complicated; winter wheat and summer maize are the main cropping systems, and there are a few fields where wheat is rotated with peanuts or soybeans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These subregions may be called management zones (MZs), representing a combination of limiting factors that determine the spatial variability of soil properties and crop yield (Mallarino & Wittry, 2004). The soil's physical and topographical characteristics, vegetation biomass, and management practices are some of the most used data in cluster analysis algorithms to define MZs due to their stability over time (Khosla et al., 2002; Lajili et al., 2021; Schenatto et al., 2016). Monocultures such as soybean [ Glycine max (L.) Merr.…”
Section: Introductionmentioning
confidence: 99%